Warszawski krąg historyków idei a recepcja światowej socjologii w Polsce. Pierwsze przybliżenie = Warsaw circle of historians of ideas and the reception of world sociology in Poland. First disclosure - Chałubiński, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article focuses on the contribution of Polish historians of ideas to the reception of western sociology in Poland after 1956. It also refers to socio-political biographies of the scientists in the Stalin and post-Stalin era. According to my opinion this period lasted longer as the most valuable works of L. Kołakowski, J. Szacki and A.Walicki were written after March 1968.
Keywords: socjologia; idea - historia; Polska